2021
DOI: 10.1093/ntr/ntab247
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electronic Nicotine Delivery Systems on Cigarette Abstinence in Smokers With No Plans to Quit: Exploratory Analysis of a Randomized Placebo-Controlled Trial

Abstract: Introduction The extent to which use of electronic nicotine delivery systems (ENDS) for smoking reduction leads to cigarette abstinence in smokers with no plans to quit smoking is unclear. This exploratory analysis examined the effects of ENDS delivering different amounts of nicotine on cigarette abstinence up to 24-week follow-up, in comparison to placebo or a behavioral substitute. Methods This four-arm parallel-group, rand… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…Regardless of the directionality, our findings show contemporaneous associations between moving from daily smoking to no smoking alongside moving from no vaping to daily vaping specifically among those who were initially not planning to quit smoking. These findings are consistent with the one other population study that evaluated this question among smokers not planning to quit [3], as well as experimental studies that have shown that giving NVPs to smokers unmotivated to quit increases their motivation to quit [4][5][6] and is associated with reductions in their cigarette smoking [6,7].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Regardless of the directionality, our findings show contemporaneous associations between moving from daily smoking to no smoking alongside moving from no vaping to daily vaping specifically among those who were initially not planning to quit smoking. These findings are consistent with the one other population study that evaluated this question among smokers not planning to quit [3], as well as experimental studies that have shown that giving NVPs to smokers unmotivated to quit increases their motivation to quit [4][5][6] and is associated with reductions in their cigarette smoking [6,7].…”
Section: Discussionsupporting
confidence: 88%
“…[3] found that daily vaping uptake was associated with eightfold greater odds of smoking cessation among those who were not planning to ever quit. These findings are consistent with experimental studies that have reported that giving NVPs to unmotivated smokers is positively associated with change in quit intentions [4, 5] and reductions in cigarette smoking [6, 7]. However, no study has yet investigated whether the association between uptake of NVP use and cigarette smoking cessation differs as a function of smokers' initial plans to quit.…”
Section: Introductionsupporting
confidence: 88%
“…Used as a harm-reduction strategy, ENDS are intended to draw smokers away from combustible cigarettes, which are the most harmful and addictive nicotine-delivery product. Consistent with these conceptual models of switching and nicotine delivery, data from observational studies 62 and randomized trials 63 , 64 support the concept that adequate levels of nicotine are likely necessary to facilitate switching away from smoking.…”
Section: Discussionmentioning
confidence: 74%
“…Consistent with other published literature on ENDS 9 , 20 , 43 , 44 , Vuse Solo was able to reduce early smoking urges to a significantly greater degree than nicotine gum, and time to maximum reduction of urges after Vuse Solo use was closer to that of smoking. Since acute nicotine cravings have been shown to lead to smoking lapse within 10 min 45 , any replacement product for CC must deliver nicotine at a sufficient rate and level so as to adequately satiate the smoker and prompt switching 46 . The pharmacokinetic results suggest that Vuse Solo can serve as an appropriate replacement product for CC among adult smokers accustomed to a fairly rapid nicotine uptake and thus a faster onset of craving relief and reductions in urge to smoke.…”
Section: Discussionmentioning
confidence: 99%